Tibetan folk tales. - Hyde-Chambers, Audrey; Hyde, Fredrick; Ralla, Kusho (Boulder Shambhala, 1981)
A collection of folk tales from one of the last ancient civilizations to be explored by the West.
Keywords: Tales -- China&delete& -- Tibet; Folklore -- China&delete& -- Tibet